The Impact of Green Human Resource Management on Employee Performance with Pro-Environment Behavior as a Mediating Variable - Andhini Kusumawardani; Andre Dwijanto Witjaksono; Anang Krisyanto (Image : Jurnal Riset Manajemen, 2025)
The Green Human Resource Management (GHRM) practices at the Environmental Department of Surabaya City Government have been applied since several years ago. However, there is still no evidence that the application of GHRM at the Environmental Department can improve overall employee performance. This research aims to analyze the influence of GHRM on employee performance with the role of employee green behaviour as a mediation variable and transformational leadership as a moderation variable using the SEM-PLS method on a sample of 171 employees of DLH Kota Surabaya. SEM-PLS was used because of its ability to obtain relationship results between variables. The results showed that GHRM practices did not have a significant effect on employee performance, although they had a positive impact on employee green behaviour. The employee green behavior failed to mediate the relationship between GHRM and employee performance. Transformational leadership has proved effective as a moderator variable in the relationship of GHRM to employee performance. To maximize the effectiveness of GHRM, there needs to be strong leadership support as well as wider involvement of the entire employee in pro-environmental practices.